Pengaruh Penambahan Tepung Temulawak (Curcuma xanthotthiza) pada Pakan Terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis niloticus) - Sintia Dehi; Arafik Lamadi; Syamsuddin Syamsuddin; Mita Alvionita (The NIKe Journal, 2026)
This study aimed to identify The Effect of Curcuma Flour (Curcuma xanthorrhiza) on Ration owards The Growth and Survival of Nile Tilapia Herrings, employing experimental method with Completely randomized design consisting of 5 treatments and 3 repetitions: treatment A Commercial Ration), B (98% of Commercial Ration + 2% of curcuma), C (96% of Commercial Ration+4% of curcuma), D (94% of Commercial Ration + 6% of curcuma) and E (92% of of Commercial Ration + 8% of curcuma). The findings revealed the highest and lowest growth of absolute length was treatment A (1.43 cm) and E (0.57 cm) respectively, while the highest and lowest growth of absolute weight was treatment B (1.31 gr) and E (0.59 gr). In addition, the highest Survival rate was treatment C and D (91.66%), while the lowest was treatment B (75%). Based on the Analysis Of Variance (ANOVA) results, the addition of curcuma flour provided significant results: F Count 3,49